2018
DOI: 10.3390/jcm7120480
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Group and Home-Based Exercise Programs in Elderly with Sarcopenia: A Randomized Controlled Trial

Abstract: Physical exercise is effective for sarcopenic elderly but evidence for the most effective mode of exercise is conflicting. The objective of this study was to investigate the effects of a three-month group-based versus home-based exercise program on muscular, functional/physical performance and quality of life (QoL) across elderly with sarcopenia. 54 elderly (47 women, 7 men aged 72.87 ± 7 years) were randomly assigned to one of three interventions: supervised group (n = 18), individualized home-based exercise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
176
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(189 citation statements)
references
References 76 publications
6
176
1
6
Order By: Relevance
“…The first one was to choose an intense educational intervention similar to that used in previous studies [51], which might have favoured the modification of beliefs about pain [112], and that was continually strengthened throughout the program with the delivery of support material [113][114][115]. The second important aspect was the fact that the intervention of the EG was applied in a group, which favoured socialization [68][69][70] and took many patients out of their social isolation. Another important component was the inclusion of games in PE, which had a powerful distracting effect and positively influenced the modification of movement patterns, allowing subjects to overcome kinesiophobia and to achieve levels of aerobic training without being aware of the intensity of the effort made, with the consequent benefits of PE at this intensity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first one was to choose an intense educational intervention similar to that used in previous studies [51], which might have favoured the modification of beliefs about pain [112], and that was continually strengthened throughout the program with the delivery of support material [113][114][115]. The second important aspect was the fact that the intervention of the EG was applied in a group, which favoured socialization [68][69][70] and took many patients out of their social isolation. Another important component was the inclusion of games in PE, which had a powerful distracting effect and positively influenced the modification of movement patterns, allowing subjects to overcome kinesiophobia and to achieve levels of aerobic training without being aware of the intensity of the effort made, with the consequent benefits of PE at this intensity.…”
Section: Discussionmentioning
confidence: 99%
“…In this line, our group designed a new intervention [67], adapting the first-line recommendations of the current clinical evidence-based guidelines [9][10][11][12][13][14] to the PC setting. Looking for a consensus on the optimal doses of PNE and PE, with a standard and cost-effective intervention and in order to optimize the resources available, a "group treatment" program was chosen, as group treatment has previously been shown to be effective [68][69][70]. Regarding the educational intervention, an intense 10 h PNE program has been designed, while the PE group program was aimed at improving functionality, social interaction, physical contact, and progressively reaching levels close to 70% of maximum aerobic capacity through playful activities (gamification), double tasks, and challenges [67].…”
Section: Introductionmentioning
confidence: 99%
“…Patients in DG of the present study received the same amount of resistance training as those in NDG. Tsekoura et al [38] have reported that supervised strengthening exercise approach to sarcopenic population is effective for improving SMI, muscle mass, and gait speed. One report on congestive heart failure patients with low muscle mass has shown improvement by resistance training [39].…”
Section: Discussionmentioning
confidence: 99%
“…The focus on the disease as being tied to the muscular system may also explain contradictory findings of non-pharmacological interventions used so far to prevent or control sarcopenia. Exercise programs show to be highly variable regarding type and mode of exercise offered [113] and result in low quality of evidence when summarized in a systematic review and meta-analysis [114]. Strength training for example, an exercise mode often used to treat sarcopenia, may not always be effective because it is not able to overcome the age-related blunted efferent neural drive plasticity [115].…”
Section: Discussionmentioning
confidence: 99%